IFPRI-Bangladesh "Dietary Patterns and Healthy Diets: What is Needed to Close the Gaps?" - Ahmed, Akhter (2018)
IFPRI Country Representative for Bangladesh Dr. Akhter Ahmed presents BIHS panel data at the Nutrition Policy Roundtable on Improving Diets to Achieve the Sustainable Development Goal.